2009
DOI: 10.1159/000252831
|View full text |Cite
|
Sign up to set email alerts
|

Lingual Nerve Morbidity and Mandibular Third Molar Surgery: A Prospective Study

Abstract: <i>Objective:</i> The objective of this study was to estimate the frequency of postoperative lingual nerve (LN) impairment after the surgical removal of mandibular third molars (M3) and to identify potential risk indicators. <i>Subjects and Methods:</i> A prospective cohort study involving 321 subjects who had 443 mandibular M3 surgically extracted at the University Hospital, Amman, Jordan. Predictor variables were categorized as patient-, anatomy- and operation-specific. The outcome va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 42 publications
1
26
0
1
Order By: Relevance
“…In the present study LNI occurred in cases which took longer time for the operation. This is in accordance with the observations of few previous studies [21,23].…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…In the present study LNI occurred in cases which took longer time for the operation. This is in accordance with the observations of few previous studies [21,23].…”
Section: Discussionsupporting
confidence: 94%
“…But adjacent to lower third molar lingual nerve is covered with only a thin layer of soft tissue and mucosa increasing the chances of injury [8,23]. Significantly higher LNI occurred in cases where lingual flap was retracted in the present study.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…The prevalence of temporary lingual nerve hypoesthesia after third molar extraction is between 2.1 and 2.5% [1-3]. The majority of the reported disturbances completely subsided during the follow-up period.…”
Section: Introductionmentioning
confidence: 99%
“…LN damage may be related to the variant anatomy in the course of the nerve and use of different surgical techniques [7] resulting in significant morbidity to the patient [8] and potential medico-legal repercussion to the surgeon [9]. Data on the LN are especially useful to new practitioners since it has been shown that inexperience on the part of the practitioner is an important factor leading to LN injury [10].…”
Section: Introductionmentioning
confidence: 99%